HOW DO FILIPINO TEACHERS INTERPRET SUSTAINABILITY DEVELOPMENT GOALS IN SCIENCE LESSON (AN INTERPRETATIVE PHENOMENOLOGICAL ANALYSIS) - Sari, Wahyu Wido; Lalas, Genesis E. (IJIET (International Journal of Indonesian Education and Teaching), 2024)
The approach of this study was to interpret the perception of Filipino teachers on Sustainable Development Goals (SDGs) in K-12 Science lessons using an Interpretative Phenomenological Analysis (IPA). The findings of this research showed linkages between Quality Education, Education for Sustainable Development, and Disaster Risk Reduction. Participant 1 (FLE) and colleagues conducted a Project-based Learning to encourage students to solve environmental problems. This resulted in a White paper submission to the International Kids Conference 2022. The project reflected a strong implementation of SDGs 1, 2, 7, 8, 9, 12, and 13. Participant 2 (NM) implemented SDGs in the form of worksheet activities with open-ended questions for students to come up with many possible answers. This resulted in a strong implementation of SDGs 2, 4, 6, 7, 9, and 13. Participant 3 (JCT) promoted students' designs on Infographics about Environmental Disasters and endorsed those in a special event that promotes Earth Days. This resulted in the implementation of SDGs 3, 13, 14, 15, and 16. The analysis showed an applied proof of improved quality of teaching through Project-based Learning that established a safe and effective learning environment, and an inspiring cooperative and transformative learning.